A Review on Fused Pyrimidine Systems as EGFR Inhibitors and Their Structure–Activity Relationship - Yadav, Tanuja T.; Moin Shaikh, Gulam; Kumar, Maushmi S.; Chintamaneni, Meena; YC, Mayur (Frontiers in Chemistry, 2022)
Epidermal Growth Factor Receptor (EGFR) belongs to the family of Tyrosine Kinase that is activated when a specific ligand binds to it. The EGFR plays a vital role in the cellular proliferation process, differentiation, and apoptosis. In the case of cancer, EGFR undergoes uncontrolled auto-phosphorylation that results in increased cellular proliferation and decreased apoptosis, causing cancer promotion. From the literature, it shows that Pyrimidine is of the most commonly studied heterocycles for its anti-proliferative activity against EGFR inhibition. The authors have tried to collate some interesting results in the heterocycles-fused pyrimidines that have been studied using different cell lines (sensitive and mutational) and in animal models to determine their activity and potency. It is quite clear that the fused systems are highly effective in inhibiting EGFR activity in cancer cells. Therefore, the Structural Activity Relationship (SAR) comes into play in determining the nature of the heterocycle and the substituents that are responsible for the increased activity and toxicity. Understanding the SAR of heterocycles-fused pyrimidines will help in getting a better overview of the molecules concerning their activity and potency profile as future EGFR inhibitors.